PENGARUH THIN CAPITALIZATION, PERTUMBUHAN PENJUAL - Nurul Hafiza; Nini Sumarni (Journal of Islamic Accounting Competency, 2025)
This research is based on the assumption that tax payments are detrimental to companies which will ultimately encourage tax avoidance practices. Where the biggest tax avoidance losses in Indonesia come from corporate taxpayers. Apart from that, there is a phenomenon of high levels of debt use in consumer cyclical companies, where this phenomenon of using debt is also found in the case of PT Rajawali Nusantara Indonesia (RNI). This research is intended to examine the impact of the variables thin capitalization, sales growth, and corporate governance on consumer cyclical company tax avoidance. The research applied is quantitative research that uses data sources in the form of secondary data. The sample collection method used purposive sampling which was carried out on consumer cyclicals companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022 with a population of 152 companies which resulted in 14 companies as samples. The total number of observations made was 70 observations. Multiple linear regression analysis is the analysis used in this research which is processed using SPSS program support. The findings from the test prove that thin capitalization, an independent board of commissioners, and an audit committee partially show no influence on tax avoidance. Meanwhile, partial sales growth shows a positive influence on tax avoidance. Simultaneously, the independent variables examined in this research show an influence on tax avoidance.